Brønsted acid-catalyzed aromatic annulation of alkoxyallenes with naphthols: a reaction sequence to larger π-conjugated naphthopyrans with aggregation-induced emission characters. Issue 4 (14th November 2018) - Zhang, Jinlong; Zhu, Lu; Shen, Kang; Yang, Huameng; Hang, Xiao-Chun; Jiang, Gaoxi
Abstract : A practical and readily scalable reaction sequence was developed for the straightforward synthesis of a new family of larger π-conjugated naphthopyrans by a Brønsted acid-catalyzed aromatic annulation of alkoxyallenes with inert naphthols. Abstract : A practical and readily scalable reaction sequence was developed for the straightforward synthesis of a new family of larger π-conjugated naphthopyrans by a Brønsted acid-catalyzed aromatic annulation of alkoxyallenes with inert naphthols. The cascade pathway involves allylation/cyclization/debenzyloxylation/isomerization/dehydration. The new class of solid state diphenylmethylene substituted naphthopyrans are fluorescent emissive and proved to have aggregation-induced emission (AIE) behavior.